Innate Mechanisms in Selective IgA Deficiency - Zhang, Jingyan; van Oostrom, Dèlenn; Li, JianXi; Savelkoul, Huub F. J. (Frontiers in Immunology, 2021)
Selective IgA deficiency (SIgAD) is the most common primary immunodeficiency expressing itself at early life. Selective IgA deficiency (IgAD), is defined as serum IgA levels at or below 0.07 g/L with normal IgM and IgG levels in individuals generally of four years of age or older. Individuals with SIgAD are largely considered to be healthy and when discovered are usually not investigated further or followed up. However, recent studies show that newborns and young infants already display clinical manifestations of this condition due to aberrancies in their immune defense. Individuals with SIgAD lack immunoglobulin (Ig) A, which is the most abundant antibody isotype in the human body and has many important functions in mucosal immune defense. Interestingly, there is a huge heterogeneity in the clinical symptoms of the affected individuals. More than 50% of the affected individuals do not have clinical symptoms, while the individuals that do show clinical symptoms can suffer from mild to severe infections, allergies and autoimmune diseases. However, the reason for this heterogeneity in the manifestation of clinical symptoms of the individuals with SIgAD is unknown. Therefore, this review focusses on the characteristics of innate immune system driving T-cell independent IgA production and providing a mechanism underlying the development of SIgAD. Thereby, we focus on some important genes, including TNFRSF13B (encoding TACI), associated with SIgAD and the involvement of epigenetics, which will cover the methylation degree of TNFRSF13B, and environmental factors, including the gut microbiota, in the development of SIgAD. Currently, no specific treatment for SIgAD exists and novel therapeutic strategies could be developed based on the discussed information.